TINGKAT KEPATUHAN MINUM OBAT ANTIDIABETES PASIEN DIABETES MELITUS TIPE II DI PUSKESMAS KARTASURA SUKOHARJO - Ifki Isnaini; Adiningsih, Retnowati; Anita Mursiany (Jurnal Kesehatan Yamasi Makassar, 2024)
Diabetes mellitus (DM) is a serious long-term (or chronic) condition that occurs when there is an increase in glucose levels in the blood because the body cannot produce enough of the insulin hormone, or cannot use the insulin it produces effectively. The aim of this study was to determine the level of compliance with taking oral antidiabetic medication in patients with type II diabetes mellitus at the Kartasura Sukoharjo Community Health Center. The research method uses descriptive quantitative with prospective data collection. The research was conducted at the Kartasura Sukoharjo Community Health Center in December 2023 - January 2024. The instrument used was MARS-5 which consists of 5 questions that describe the patient's level of medication adherence. The sampling technique used purposive sampling (non probability sampling) of 120 samples. Based on the research results obtained, it can be concluded that the level of compliance with taking antidiabetic medication for type II diabetes mellitus patients is in the high level of compliance category with 9 respondents (7.5%), the medium level of compliance category is 111 respondents (92.5%), category low compliance level of 0 respondents (0%).